Novel graphene‐based transparent electrodes for perovskite solar cells. (9th October 2018) - Iqbal, Tahir; Haqnawaz, Muhammad; Sultan, Muhammad; Tahir, Muhammad Bilal; Khan, Muhammad Isa; Riaz, Khalid Nadeen; Ijaz, Mohsin; Rafique, Muhammad
Summary: Transparent nanoelectrodes based on reduced graphene oxide/tin oxide (RGO/SnO2 ) composite have been prepared for perovskite solar cells. Graphene oxide (GO) was synthesized by chemical route using modified Hummer's method and SnO2 solution by sol‐gel method separately. The five layers of SnO2 and nanocomposite solution of GO/SnO2 have been deposited on ITO substrate at 3000 rpm for 90 seconds. The prepared samples were heated at 500°C under the flow of argon gas for 1 hour. It was found that GO/SnO2 electrodes have transparency more than 84%, minimum resistance R  = 3 MΩ, and voltage drops across thin film V  = 0.087 mV. In order to characterize the sample, the X‐ray diffraction spectroscopy has been used for the analysis of face structure and symmetry of SnO2, GO, RGO, and GO/SnO2 nanocomposites. Ultraviolet visible (UV‐visible) spectroscopy provided information about transmission, absorbance, and reduction of band gap due to intermixing of graphene/SnO2 nanocomposites. The FTIR characterization provided information about the attachment of SnO2 on graphene sheets. Four‐point probes have been used to analyze the resistance and voltage drop across each sample. Surface analysis of SnO2 and elemental composition has been done by XPS. These results regarded as a new way to analyze the SnO2 /graphene‐based electrodes and suggest their applications for various environmental issues and to overcome energy crisis of the world.